Circulating CTRP1 Levels Are Increased and Associated with the STOD in Essential Hypertension in Chinese Patients - Zhengjia Su; Shuya Tian; Wei Liang (Cardiovascular Therapeutics)
This study aimed to investigate the correlation between complement C1q tumor necrosis factor-related protein 1 (CTRP1) and subclinical target organ damage (STOD) in essential hypertension (EH). 720 patients were enrolled in this study, including 360 healthy subjects and 360 patients with EH. The EH group included 183 patients complicated with STOD and 177 patients without STOD. In the STOD group, there were 87 patients with left ventricular hypertrophy (LVH), 32 patients with microalbuminuria (MAU), and 58 patients with complication of LVH and MAU. Enzyme-linked immunosorbent assay (ELISA) was used to detect the CTRP1, adiponectin (APN), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). We found that CTRP1 levels were higher in patients with EH than those in healthy subjects; moreover, the level of CTRP1 of patients in the group complicated with EH and STOD was increased compared with EH patients without STOD. CTRP1 levels in the group complicated with LVH and MAU were significantly higher than those in the LVH group and the MAU group. Furthermore, APN, CTRP1, and IL-6 were three factors that influenced the STOD of EH patients, among which CTRP1 and IL6 were positively related with the complication of hypertension and STOD. In conclusion, CTRP1 levels are increased and associated with the STOD (heart and kidney) in essential hypertension, which can be regarded as a novel biomarker in the prediction of prognosis for patients with essential hypertension.